TIK dan Pembelajaran Bahasa Asing: Sebuah Ringkasan - Asep Budiman (Tarling : Journal of Language Education, 2020)
During this COVID-19 pandemic, most work in the world is done online, including the teaching and learning process. Online learning is generally accommodated with the use of Information and Communication Technology (ICT) which covers a range of tools, methods, and activities. This article describes the use of ICT as it relates to the theory of language learning and then discusses principles for selecting tools and platforms which can be used to enhance language learning. In addition, the kinds of tools available for teachers and learners are highlighted. Having completed the article, the readers will hopefully gain an awareness that ICT helps improve language learning, that making decisions on selecting appropriate digital tools is vital, and that language learning can be done through digital work.